(untitled) (Research, Society and Development, 2022)
Cosmetics are substances, mixtures, or formulations used to improve or protect the appearance or odor of the human body. In Brazil, they are included in a category called “cosmetics, personal care products, and perfumes”. This worked aimed to evaluate cosmetic notifications registered by NOTIVISA through a retrospective study, in the period of 2006 to 2016. There were 1484 notifications of products for adult use, with 88.7% technical complaints and 11.3% adverse events. The historical distribution was heterogeneous, with peaks in the years 2009, 2012, 2013, and 2015, which concentrated 58.7% of notifications. The highest impact was in the Southeast (50.7%) and South (20.8%) regions, which concentrated approximately 71.5% of the total notifications. Cosmetics with risk level 2 were the most recurrent (51.3%). The products most notified due to technical complaints were antiseptic hand gels (213) and for adverse events were products for straighten and/or dyed hair (37). These data indicate the importance of monitoring such products, concerning good production practices, as well as the safety and risk assessment in their registration. Systematic surveillance of the use of these products is essential to prevent the occurrence of such injuries.